2019
DOI: 10.1167/tvst.8.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Biological Characteristics of Subsilicone Oil Fluid and Differences With Other Ocular Humors

Abstract: Purpose: Subsilicone oil fluid (SOF) in eyes with silicone oil (SO) endotamponade possibly has a role in complications (e.g., vision loss); thus, we aimed to examine inflammatory cytokine and electrolyte levels and retinal glial cell viability in SOF. Methods:We measured major inflammatory cytokine levels and electrolytes in SOF and compared them with those in vitreous fluid (VF) and anterior chamber fluid (ACF). We analyzed the correlation between inflammatory cytokines and retinal thickness in SO-filled eyes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 52 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…Several reports said that SO in the anterior chamber or SO in contact with corneal endothelium had the adverse effect on the corneal endothelial cells [16][17][18] . It was also reported that the intraocular fluid from SO tamponade patients contained higher concentrations of inflammatory cytokines when SO was present compared to after SO removal 23 . However, no correlation was observed between CEC loss and the existence of anterior chamber SO in our study.…”
Section: Discussionmentioning
confidence: 92%
“…Several reports said that SO in the anterior chamber or SO in contact with corneal endothelium had the adverse effect on the corneal endothelial cells [16][17][18] . It was also reported that the intraocular fluid from SO tamponade patients contained higher concentrations of inflammatory cytokines when SO was present compared to after SO removal 23 . However, no correlation was observed between CEC loss and the existence of anterior chamber SO in our study.…”
Section: Discussionmentioning
confidence: 92%
“…To the best of our knowledge, only three published reports have assessed vitreous iron concentrations of the human eyes. These studies analyzed medical–legal autopsy samples [ 43 ] and examined the biochemical composition of living patients [ 44 , 45 ]. Compared with their respective average iron concentrations, OT samples in our study may have a lower iron concentration.…”
Section: Discussionmentioning
confidence: 99%